1985
DOI: 10.1007/bf00162004
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of ocular findings in patients treated with PUVA

Abstract: Photochemotherapy combined with psoralen, now widely used in the treatment of psoriasis, vitiligo, Andrews' disease and some other skin conditions, has been accepted as one of the potential factors that might contribute to the development of cataract. This view is based upon experimental animal studies. In the present study 408 patients receiving PUVA treatment in the period between 1977 and 1983 have been followed up for up to 6 years after the initiation of therapy. Repeated ophthalmological examinations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In all such cases the ages of patients were younger than 55 years except in the study of Lerman et al 90 where patient ages were not reported. 81,84,91,92 This finding supports the hypothesis that in younger lenses, the gamma-crystalline fraction of the lens proteins are more sensitive to UV light than in older lenses. 93 …”
Section: Lenssupporting
confidence: 85%
“…In all such cases the ages of patients were younger than 55 years except in the study of Lerman et al 90 where patient ages were not reported. 81,84,91,92 This finding supports the hypothesis that in younger lenses, the gamma-crystalline fraction of the lens proteins are more sensitive to UV light than in older lenses. 93 …”
Section: Lenssupporting
confidence: 85%
“…18,19 In addition, other older studies failed to reveal any substantial risk of ocular damage related to PUVA therapy. [12][13][14][15][16][17] However, there are some isolated reports that, even if they cannot prove a relation between PUVA exposure and an increase risk of eye damage, they are a source of concern regarding PUVA treatment safety. 3,7,11 These studies examined a small number of patients and often for a limited period, so their power to detect any potential risk for cataract formation is low.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Different definitions of cataract have been used in various studies and, with exception of our prior publications, most of them had a limited period of follow-up and studied small numbers of patients. 2,18,19 The PUVA follow-up study was organized to determine the long-term safety of this and other psoriasis treatments.…”
mentioning
confidence: 99%
“…In-vitro studies of human lenses showed that the gamma crystalline fraction of the lens proteins of a young lens is much more sensitive to ultraviolet light than other fractions in the same lens or the same fractions in older lenses [7]. On the basis of mor- [5] 96 -Tegner '83 [13] 302 -Sterk '83 [12] 42 (1) Boukes '85 [1] 408 3 Recchia '86 [9] 200 -6 studies 1.094 3 (4) phological study, with the help of Scheimpflug lens-photography and densitometry, three age groups can be distinguished for the non-cataractous aging of the lens: up to 35 years (clear), 35 to 55 years (slight decrease in transparency, slight increase in thickness of lens) and above 55 years (more pronounced loss of transparency and further increase in thickness of lens) [11].…”
Section: Introductionmentioning
confidence: 99%